Partial ear canal ablation and lateral bulla osteotomy in rabbits. (28th February 2013) - Eatwell, K.; Mancinelli, E.; Hedley, J.; Keeble, E.; Kovalik, M.; Yool, D. A.
Abstract : Six lop rabbits were presented with clinical signs of otitis media or externa. The presence of disease was confirmed by computerized tomography examination, with two rabbits suffering from bilateral disease. The rabbits were anaesthetized and underwent surgery of the affected bulla. Rabbits with bilateral disease had a minimum of 2 weeks between procedures. A single vertical incision was made over the base of the vertical canal, which was bluntly dissected free from surrounding tissue. The ventral portion of the vertical canal was removed and a lateral bulla osteotomy was performed. The mucosa at the base of the dorsal vertical canal was apposed and the aural cartilage sutured to form a blind‐ending pouch open at the pretragic incisure. Histopathological samples taken from the dorsal margin of the vertical canal yielded subtle and non‐specific changes in the six samples submitted. All rabbits were discharged within 48 hours of surgery. The cosmetic outcome was excellent with animals retaining visually normal aural anatomy. The partial ear canal ablation/lateral bulla osteotomy procedure is quick and has a good cosmetic result when performed in rabbits.